Combined Conventional Synthetic Disease Modifying Therapy vs. Infliximab for Rheumatoid Arthritis: Emulating a Randomized Trial in Observational Data. Issue 4 (23rd June 2022) - Barbulescu, Andrei; Askling, Johan; Saevarsdottir, Saedis; Kim, Seoyoung C.; Frisell, Thomas
Abstract : Observational studies are often considered unreliable for evaluating relative treatment effectiveness, but it has been suggested that following target trial protocols could reduce bias. Using observational data from patients with rheumatoid arthritis (RA) in the Swedish Rheumatology Quality Register (SRQ), between 2006 and 2020, we emulated the protocol of the Swedish Farmacotherapy trial (SWEFOT) and compared the results. SWEFOT was a pragmatic trial nested in SRQ, between 2002 and 2005, where methotrexate (MTX) insufficient responders were randomized to receive additional infliximab or sulfasalazine (SSZ) + hydroxychloroquine (HCQ). Patients with RA initiating infliximab ( N = 313) or SSZ + HCQ ( N = 196) after MTX were identified in SRQ and the Prescribed Drugs Register, mimicking the SWEFOT eligibility criteria. The primary outcome was the proportion of European Alliance of Associations for Rheumatology (EULAR) good responders at 9 months, classifying patients who discontinued treatment as "nonresponders." Through sensitivity analyses, we assessed the impact of relaxing eligibility criteria. The observed proportions reaching EULAR good response were close to those reported in SWEFOT: 39% (vs. 39% in SWEFOT) for infliximab and 28% (vs. 25%) for SSZ + HCQ. The crude observed response ratio was 1.39 (95% confidence interval (CI) 1.04–1.86), increasing to 1.48 (95% CI 0.98–2.24) after confounding adjustment, compared to 1.59 (95% CI 1.10–2.30) in SWEFOT. Results remained close to SWEFOT when relaxing eligibility criteria until allowing prior disease‐modifying anti‐rheumatic drug (DMARD) use which reduced the observed difference between treatments. By applying a prespecified trial emulation protocol to observational clinical registry data, we could replicate the results of SWEFOT, favoring infliximab over SSZ + HCQ combination therapy at 9 months.